Modern Thermal Energy Storage Systems Dedicated to Autonomous Buildings - Musiał, Michał; Lichołai, Lech; Katunský, Dušan (Energies (Basel), 2023)
This paper presents a detailed analysis of the research into modern thermal energy storage systems dedicated to autonomous buildings. The paper systematises the current state of knowledge concerning thermal energy storage systems and their use of either phase change materials or sorption systems; it notes their benefits, drawbacks, application options, and potential directions for future development. The rapid proliferation of studies on installation systems, new composites, and phase change materials requires a systematisation of the subject related to short- and long-term thermal energy storage in building structures. This paper focuses on assessing the validity of the current improved thermal energy storage solutions for buildings with very high energy efficiency standards and buildings that are energy-independent. The paper presents the current results of the energy and economic analyses of the use of heat storage systems in buildings. This paper shows the optimal heat storage systems for autonomous buildings. Moreover, it also shows other potential ways to develop systems and composites capable of storing heat in autonomous buildings.